A Tensioned Human Skin Explant Model Used for Preliminary Assessment of Chemexfoliant-Stimulated Bioeffects - Michael J. Conneely; Jin Namkoong; Francis Allison; S. Kyoko Hirata Tsutsumi; Dominic Grussu; Ryan Willis; Kyle Henderson; Paul A. Campbell; Melissa Moy; Ewelina Lesniak; Joanna Wu; Robyn P. Hickerson (JID Innovations)
A tensioned ex vivo full-thickness human skin explant platform was used to assess the bioeffects arising from application of several commercial chemexfoliation agents. Although such treatments are well-established, and improved understanding of the underlying mechanistic processes continues to emerge, research into the optimum treatments for specific skin types/conditions is still needed for enhanced efficacy while minimizing recovery time. The 3 commercial chemexfoliation agents employed all contained trichloroacetic acid at well-defined concentrations (6, 10, and 20%) and were applied to the explants’ stratum corneum. Subsequently, measurements of dermal remodeling factors (COL1A1, ELN, HAS2, HAS3, and procollagen type I) and inflammatory marker (IL-1b) were undertaken using qPCR and immunofluorescent analyses. Statistical analysis of these data facilitated the establishment of benchmarking biological responses to these trichloroacetic acid–containing agents against untreated controls. The performance of an innovative trichloroacetic acid–free chemexfoliation agent was then measured and, upon comparison with the previous benchmarking data, indicated that dermal remodeling factors could be upregulated in fashion comparable with that of the trichloroacetic acid–containing agents but with significant suppression of inflammatory response. Our measurements thus underscore the promise of the tensioned explant over prolonged study periods and also that potentially valuable insights to guide preclinical strategies may be forthcoming from the protocol developed.